A Feasibility study on the Electronic Motor Saver - Camacho, Rowena Grace D. (College of Engineering, 2001)
The study focused on the production of Electronic Motor Saver (EMS). EMS is a device which is connected to an air-conditioning unit. This device saves energy and, at the same time, lengthens the life of the connected appliance. The marketing, technical, financial viability of producing the EMS was conducted. Furthermore, the organizational structure and the socio-economic impact of putting up the EMS project was studied. In accomplishing all this, establishing the over-all feasibility of the EMS was established. In the marketing study identified the target market of the said product, it was concluded that the EMS will be sold to households and small and micro-establishments in the Metropolitan Manila Area. The targeted income bracket are those households there exists a considerable demand for the product, and thus a dynamic marketing strategy was conceptualized in order to capture the identified target market. For the technical study probed into the detailed production process required to produce the EMS. In the over-all analysis, it was established that producing the EMS is technically feasible. The manpower, facilities and costing requirements were established as well. The financial study analyzed key indicators to verify the EMS project's capability to fulfill and meet its projected financial obligations. Various indicators were also used in order to show the viability of the project. All indicators pointed to a positive outlook for the EMS project. Therefore, it was established that the EMS is financially viable. The social profitability study, on the other hand, proved that the EMS project is not merely financially profitable, but also environmentally and socially sound. The micro and macro-economic aspects of the EMS were analyzed and both results showed positive outcome. Thus, over-all social and economic impact proved to be favorable. Therefore, the study strived to ascertain if the EMS is actually worth producing. The basic premise was that there was a need for the EMS. All aspects were studied and virtually exhausted. In the final analysis, the overwhelming conclusion is that the EMS should be produce since it is feasible.